2020
DOI: 10.1186/s43008-019-0022-6
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of Pterulaceae Corner (Basidiomycota: Agaricales) introducing the ant-associated genus Myrmecopterula gen. nov., Phaeopterula Henn. and the corticioid Radulomycetaceae fam. nov.

Abstract: Pterulaceae was formally proposed to group six coralloid and dimitic genera: Actiniceps (=Dimorphocystis), Allantula, Deflexula, Parapterulicium, Pterula, and Pterulicium. Recent molecular studies have shown that some of the characters currently used in Pterulaceae do not distinguish the genera. Actiniceps and Parapterulicium have been removed, and a few other resupinate genera were added to the family. However, none of these studies intended to investigate the relationship between Pterulaceae genera. In this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Sequences of the specimen of P. gracile collected by us (IO.14.142) were identical to those obtained from the available genome of P. gracile (CBS 309.79) ( Fig. 3 ), employed also by Leal-Dutra et al. (2020) .…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Sequences of the specimen of P. gracile collected by us (IO.14.142) were identical to those obtained from the available genome of P. gracile (CBS 309.79) ( Fig. 3 ), employed also by Leal-Dutra et al. (2020) .…”
Section: Resultssupporting
confidence: 56%
“… Leal-Dutra et al. (2020) , using one of the specimens of P. gracile employed in our analyses (CBS 309.79), showed that it belongs to the Pterulicium clade.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations